Anthropogenic inputs of heavy metals in the east part of the Johore Straits as revealed by their concentrations in the different soft tissues of Perna viridis (L.) - Yap, Chee Kong; Sulaiman, Mohd. Nasir; Edward, Franklin Berandah; Tan, Soon Guan (Universiti Putra Malaysia Press, 2012)
Concentrations of Cd, Cu, Ni, Pb and Zn were determined in seven different soft tissues of Perna viridis collected in May-November 2006 from the six sites in the Straits of Johore. The metal concentrations in the soft tissues of the samples from the east of the Johore Causeway were generally higher than those of the samples collected from the western partI of it. This indicated that the eastern part of the straits had higher contamination and bioavailabilities of Cd, Cu, Ni, Pb and Zn. Therefore, these results are in agreement with the fact that there are various anthropogenic activities, such as petrochemical plants and port activities, in the eastern part of the Straits of Johore. The findings of this work are useful for future reference, particularly for the semi-enclosed Straits.